Aberrant interhemispheric homotopic functional and structural connectivity in amyotrophic lateral sclerosis. Issue 5 (2nd December 2016) - Zhang, Jiuquan; Ji, Bing; Hu, Jun; Zhou, Chaoyang; Li, Longchuan; Li, Zhihao; Huang, Xuequan; Hu, Xiaoping
Abstract : Objective: Amyotrophic lateral sclerosis (ALS) is an idiopathic and fatal neurodegenerative disease of the human motor system. While microstructural alterations in corpus callosum (CC) have been identified as a consistent feature of ALS, studies directly examining interhemispheric neural connectivity are still lacking. To shed more light on the pathophysiology of ALS, the present study aims to examine alterations of interhemispheric structural and functional connectivity in individuals with ALS. Methods: Diffusion tensor imaging (DTI) and resting-state functional MRI (rfMRI) data were acquired from 38 individuals with ALS and 35 gender-matched and age-matched control subjects. Indices of interhemispheric functional and structural neural connection were derived with analyses of voxel mirrored homotopic connectivity (VMHC) and probabilistic fibre tracking. Results: The rfMRI has revealed extensive reductions of VMHC associated with ALS in brain regions of the precentral and postcentral gyrus, the paracentral lobule, the superior temporal gyrus, the middle cingulate gyrus, the putamen and the superior parietal lobules. With DTI, the analysis has also revealed reductions of interhemispheric structural connectivity through the CC subregions II, III and V in patients with ALS. Additionally, interhemispheric functional connectivity of the bilateral precentral gyri positively correlated with fractional anisotropy values of the CC subregion III, which structurally connects the bilateral motor cortices. Conclusions: The present data provided direct evidence confirming and extending the view of impaired interhemispheric neural communications mediated by CC, providing a new perspective for examinations and understanding the pathophysiology of ALS.